The Effect of Corporate Governance, Innovation, and Supporting Factors towards Competitive Advantages of Batik SMEs in The Pandemic - Pasaribu, Hiras; Karyono, Karyono; Suhascaryo, H. KRT. Nur; Sirait, Suwanto (RSF Conference Series: Business, Management and Social Sciences, 2021)
The obstacle for Batik creative industries in the time of the Covid-19 pandemic is that it is not easy to reach the market. Because before the pandemic, the agencies, buyers, and consumers could come to the places where the products were made. In order to get out of this difficulty, business actors must adapt to do innovations, among them by using business digitalization technology, so that the market scope will be wider, and build up innovation that the quality of the product can be competitive. In order for SMEs to be quickly adapted in time of the covid-19 pandemic, they must join to form a community portal of batik industry activators. The aim of this research is to know the effect of Corporate Governance, Product Innovation, Business digitalization, and Effectiveness of Management Control towards Competitive Advantages of SMEs of Creative Industry of Batik Craftsman in Regency and City in Yogyakarta. The method of research used is a survey method to 55 managers of 127 SMEs of the Creative Industry of Batik Craftsman in all regencies and cities in Yogyakarta. The collection of primary data uses Questionnaires with the Likert Scale. In accordance with consideration data value and hypotheses, this research uses suitable statistical analysis that is the Partial Least Square (PLS) method. This method will reveal the amount of independent variable effect on dependent variables. The result of the research shows that corporate governance is not significantly influential on Competitive Advantages of SMEs, while Product Innovation, The Use of business digitalization-based information technology, and Effectiveness of Management Control bring positive effects toward Competitive Advantages. The Dominant Variable is the product innovation, while the effect of the lowest variable towards Competitive Advantages is the Effectiveness of Management Control.